Blocking glutamate mGlu5 receptors with the negative allosteric modulator CTEP improves disease course in SOD1G93A mouse model of amyotrophic lateral sclerosis. (29th June 2021) - Milanese, Marco; Bonifacino, Tiziana; Torazza, Carola; Provenzano, Francesca; Kumar, Mandeep; Ravera, Silvia; Zerbo, Arianna Roberta; Frumento, Giulia; Balbi, Matilde; Nguyen, T. P. Nhung; Bertola, Nadia; Ferrando, Sara; et al.
Abstract : Background and Purpose: The pathogenesis of amyotrophic lateral sclerosis (ALS) is not fully clarified, although excessive glutamate (Glu) transmission and the downstream cytotoxic cascades are major mechanisms for motor neuron death. Two metabotropic glutamate receptors (mGlu1 and mGlu5 ) are overexpressed in ALS and regulate cellular disease processes. Expression and function of mGlu5 receptors are altered at early symptomatic stages in the SOD1 G93A mouse model of ALS and knockdown of mGlu5 receptors in SOD1 G93A mice improved disease progression. Experimental Approach: We treated male and female SOD1 G93A mice with 2‐chloro‐4‐((2, 5‐dimethyl‐1‐(4‐(trifluoromethoxy)phenyl)‐1 H ‐imidazol‐4‐yl)ethynyl)pyridine (CTEP), an orally available mGlu5 receptor negative allosteric modulator (NAM), using doses of 2 mg·kg −1 per 48 h or 4 mg·kg −1 per 24 h from Day 90, an early symptomatic disease stage. Disease progression was studied by behavioural and histological approaches. Key Results: CTEP dose‐dependently ameliorated clinical features in SOD1 G93A mice. The lower dose increased survival and improved motor skills in female mice, with barely positive effects in male mice. Higher doses significantly ameliorated disease symptoms and survival in both males and females, females being more responsive. CTEP also reduced motor neuron death, astrocyte and microglia activation, and abnormal glutamate release in the spinal cord, with equal effects in male and female mice. No differences were also observed in CTEP access to the brain. Conclusion and Implications: Our results suggest that mGlu5 receptors are promising targets for the treatment of ALS and highlight mGlu5 receptor NAMs as effective pharmacological tools with translational potential.